2021
DOI: 10.1016/j.cell.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Dual film-like organelles enable spatial separation of orthogonal eukaryotic translation

Abstract: Summary Engineering new functionality into living eukaryotic systems by enzyme evolution or de novo protein design is a formidable challenge. Cells do not rely exclusively on DNA-based evolution to generate new functionality but often utilize membrane encapsulation or formation of membraneless organelles to separate distinct molecular processes that execute complex operations. Applying this principle and the concept of two-dimensional phase separation, we develop film-like syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 119 publications
(169 reference statements)
0
34
0
Order By: Relevance
“…However, one downside of this technique is that it is not mRNA-specific, leading to potential background labeling of untargeted proteins with their naturally occurring stop codons being suppressed. To tackle this problem, we utilized our recently developed synthetic orthogonally translating (OT) film-like organelles to form a distinct protein translational machinery on the outer mitochondrial membrane surface ( 36 ). These organelles exclusively reassigned two Amber codons for the target FG-NUP and incorporated TCO*A at the two specified sites with high selectivity, ensuring minimal interference for endogenous protein translation and negligible background staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, one downside of this technique is that it is not mRNA-specific, leading to potential background labeling of untargeted proteins with their naturally occurring stop codons being suppressed. To tackle this problem, we utilized our recently developed synthetic orthogonally translating (OT) film-like organelles to form a distinct protein translational machinery on the outer mitochondrial membrane surface ( 36 ). These organelles exclusively reassigned two Amber codons for the target FG-NUP and incorporated TCO*A at the two specified sites with high selectivity, ensuring minimal interference for endogenous protein translation and negligible background staining (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This study has several antecedents, though it differs from them in significant ways. An elegant set of studies by Lemke and coworkers showed that a synthetic RNPG 70,71 could successfully recruit a target mRNA to a protein condensate to spatially limit the incorporation of non-canonical amino acids in the protein encoded by the mRNA within the condensate, but they used a naturally occurring IDP with a limited range, and thus tunability, of phase behavior. Navarro et al used Pum1, a homolog of Pum2, to sequester endogenous mRNA into a synthetic condensate 28 .…”
Section: Discussionmentioning
confidence: 99%
“…52−54 The potential for incorporation in response to endogenous amber codons can be partially prevented by the cellular compartmentalization of the mRNA using liquid-phase segregation or membrane recruitment. 55,56 However, the problem of cells incorporating natural amino acids at TAG codons is well known, particularly for Phe and Tyr analogues. Though background-causing amino acids may be dropped out of the media in E. coli, 11,57 methods for addressing this problem in eukaryotic species have not been reported.…”
Section: ■ Introductionmentioning
confidence: 99%